Case report: Progressive skin rash and lymphadenopathy associated with lamotrigine−valproic acid combination in a bipolar adolescent - Duan, Yingxu; Qiu, Fangxinrui; Zhou, Jingyuan; Liu, Shiyu; Zhao, Die; Qiu, Changjian (Frontiers in Pharmacology, 2023)
Background: Lamotrigine may cause severe skin reactions. There is a known interaction between lamotrigine-valproic acid with an increase in lamotrigine levels and increase in lamotrigine toxicity risk. Few cases of severe rash and systemic reactions in bipolar patients using lamotrigine and valproate have been reported. Here, we report a rare case of severe skin rash and lymphadenopathy associated with lamotrigine-valproic acid combination. Case presentation: An 18-year-old female with bipolar disorder type I was treated with lamotrigine, magnesium valproate, and perospirone for 12 days. After the last dose of lamotrigine, she abruptly developed generalized rash and swollen lymph nodes which continued to progress over the next 3 days. This finally subsided after stopping valproate and with glucocorticoid treatment. Conclusions: This case suggests that lamotrigine-valproic acid combination may cause not only rash but also lymphadenopathy. Even though the above reactions appear after the last dose of lamotrigine, it cannot be ruled out as suspicious. We recommend caution during titration of lamotrigine and valproate and early withdrawal of both when signs of hypersensitivity appear.